Can we (and should we) cure aging? - Tadinac, Meri (Array, 2012)
One of the imperatives of modern life is to be beautiful, which in most cases means to look young. Myriads of treatments are being proposed as the panacea for the visible symptoms of aging. However, even if we look younger, it does not mean that we have stopped aging. We have only succeeded to slow down some aspects of senescence - a process of bodily deterioration occurring at older ages. The modern medicine and modern technologies have enabled us to do that, and they go even further using hormone injections and “wonder” supplements. Although the average length of life in modern societies has steadily increased during the past few hundred years, the maximum duration of life has not – inevitably we age and die. Our bodies and especially our brain can be viewed as the miracle of evolution, so why has evolution not eliminated the process of senescence which is so devastating to our fitness? From the perspective of the evolutionary theory and Darwinian medicine arises an interesting answer to this question. Natural selection makes organisms that maximize their reproductive success, even at the expense of individual happiness, health and longevity (Nesse, 2001). Some research indicates that the maintenance of the organism after the age of reproduction is not favoured by natural selection, and that sexual reproduction selects for mechanisms that increase the fitness in youth, at the cost for the organism in older age. In other words, as the pleiotropic theory of senescence suggests, the genes with early benefits contribute to senescence. Considerable laboratory evidence on various species is in favour of this explanation. It seems that mechanisms causing senescence might not be evolutionary mistakes, but compromises carefully chosen by natural selection. Therefore, senescence is not a disease that could be cured if only the scientists made the necessary additional efforts in finding and combating its causes. The best we can hope for are research breakthroughs in the prevention and postponement of some diseases of senescence, so that we could more fully enjoy our senior years. The fountain of youth, at least from the evolutionary point of view, remains just a myth.